Dreams in group psychotherapy : theory and technique - Neri, Claudio; Pines, Malcolm; Friedman, Robi (International library of group analysis, 2002)
Dreams told in the group are conjoint individual and group creations. They are both influenced by the group atmosphere and may in turn influence it and the individual, promoting change and development. Dreams have a deepening effect on therapeutic work and, due to their unconscious content, they may represent the most authentic exchange between individual and group. This state-of-the-art book provides help for therapists encountering a dream told in their group. It covers the major theoretical perspectives for their understanding, as well as representing different psychological schools and the.